The Analysis of Financing in the Agricultural, Forestry, and Agricultural Infrastructure Sectors in BPRS in Indonesia - Safira, Cut Maza; Ansari, Leli Putri; Risma, Okta Rabiana; Ariani, Dian; Suhendra, Noval (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The agriculture, forestry, and agricultural infrastructure sector plays a crucial role in maintaining Indonesia’s food security, yet it continues to face various challenges, especially in terms of limited access to financing. Sharia Rural Banks (BPRS) are among the financial institutions that have the capacity to provide funding to this sector, although the distribution of such financing is affected by both internal and external factors. This study aims to analyze the influence of Non-Performing Financing (NPF), Third Party Funds (DPK), and the Farmer Exchange Rate (NTP) on BPRS financing in the agriculture, forestry, and agricultural infrastructure sectors in Indonesia. Using monthly time series data from January 2013 to September 2024, the study applies the Autoregressive Distributed Lag (ARDL) approach to explore both short-run and long-run relationships. The findings indicate that NPF has a negative and statistically significant effect in both the short and long term. DPK, while showing an insignificant effect in the short term negative in the previous period and positive in the current exhibits a significant and positive influence over the long term. Meanwhile, NTP exerts a positive but statistically insignificant impact across both time horizons. These results provide important insights into the variables affecting BPRS financing and offer useful input for policy development aimed at strengthening the targeted sectors through Islamic financial approaches.